HRM and Small-Firm Employee Motivation: Before and after the Recession - Alex Bryson; Michael White (Institute of Labor Economics (IZA), 2017)
A long-running debate in the small firms' literature questions the value of formal 'human resource management' (HRM) practices which have been linked to high performance in larger firms. We contribute to this literature by exploiting linked employer-employee surveys for 2004 and 2011. Using employees' intrinsic job satisfaction and organizational commitment as measures of motivation we find the returns to small firm investments in HRM are u-shaped. Small firms benefit from intrinsically motivating work situations in the absence of HRM practices, find this advantage disturbed when formal HRM practices are initially introduced, but can restore positive motivation when they invest intensively in HRM practices in a way that characterizes 'high performance work systems' (HWPS) and 'strategic human resource management' (SHRM). Although the HPWS effect on employee motivation is modified somewhat by the recessionary transition, it remains rather robust and continues to have positive promise for small firms.
Keywords: L23; M50; M54; 330; small firms; human resource management; high performance work system; workplace motivation; intrinsic job satisfaction; organizational commitment